Synthesis, structure–property relationships and absorbance modulation of highly asymmetric photochromes with variable oxidation and substitution patterns. Issue 22 (11th October 2022) - Uno, Kakishi; Kim, Dojin; Bucevicius, Jonas; Bossi, Mariano L.; Belov, Vladimir N.; Hell, Stefan W.
Abstract : Asymmetric 1, 2-diarylperfluorocyclopentenes with "inverse" photochromism (due to shorter conjugation path in the closed-ring isomer), rapid switching and large absorption modulation are reported. Abstract : Asymmetric diarylethenes with benzo[ b ]thiophen-3-yl and 2-thienyl residues having variable oxidation degrees (S and/or SO2 ) remained unexplored. These photochromes provide reversibly photoswitchable absorbance and multicolor emission modulation. Here we report 18 photochromic 1, 2-diarylperfluorocyclopentenes with oxidized and non-oxidized 2-methylbenzo[ b ]thiophen-3-yl, as well as 5-aryl-3-methylthiophen-2-yl groups. The structure–property relationships were studied for three groups of compounds: non-oxidized, mono-oxidized (to SO2 in the benzothiophene part), and fully-oxidized (to 2 × SO2 ). The quantum chemistry calculations helped to interpret the substituents' effects in each group and predict the photophysical properties of yet unavailable photochromes. The photochromic systems with absorbance modulation introduced in this work were designed for the use in diffraction-unlimited writing and reading with light, nanopattering and optical lithography.